Teknik Pemeriksaan Radiografi Os Femur pada Kasus Fraktur Femur di Instalasi Radiologi RSUP Dr. Sardjito - Adel Amanda; Muhammad Za’im; Fisnandya Meita Astari (Jurnal Kesehatan Amanah, 2025)
Examination of the femur bone for femur fracture at the Radiology Installation of RSUP dr. Sardjito Yogyakarta was performed using a lateral projection with the central ray angled 30 degrees towards the cranial direction. However, according to several theories, it is stated that the use of lateral projection does not involve angling the central ray. The purpose of this study is to understand the examination procedure for femur bone fractures and the reasons for using the lateral projection at the Radiology Installation of RSUP dr. Sardjito Yogyakarta. The research method used in this study is qualitative research with a descriptive method and a case study approach. The research was conducted at the Radiology Installation of RSUP dr. Sardjito Yogyakarta in February-March 2025 with research subjects consisting of 3 radiographers and 1 radiology specialist doctor. The data collection methods used were observation, interviews, documentation, and literature study. Data analysis was carried out by data collection, data reduction, data presentation, and then conclusions were drawn. The results of the study show how radiographic examination of the femur in fracture cases at RSUP dr. Sardjito uses Anteroposterior and Lateral Crosstable projections to obtain optimal visualization of the anatomy of the femur, especially in uncooperative patients. The Lateral Crosstable technique was chosen because it allows clearer visualization of the proximal part of the femur without having to move the injured extremity.